Observed Intraseasonal Oceanic Variations in the Eastern Equatorial Indian Ocean and in the Outflow Straits of the Indonesian Throughflow - Iskhaq Iskandar; Yukio Masumoto; Keisuke Mizuno (Journal of Mathematical and Fundamental Sciences, 2010)
The observed currents in the eastern equatorial Indian Ocean and in the outflow straits of the Indonesian Throughflow (ITF) are shown to have significant intraseasonal variations and coherency during January 2004 "“ November 2006. The wavelet analysis between the eastern equatorial Indian Ocean and the ITF straits demonstrates significant intraseasonal coherency for the observed current at 50m depth. At 150m depth, the intraseasonal coherency only occurs between the observed currents in the eastern equatorial Indian Ocean and in the Lombok and Ombai Straits. On the other hand, at 350m depth the intraseasonal coherency is only found between the eastern equatorial Indian Ocean and the Ombai Strait. This intraseasonal coherency is associated with the wind-forced equatorial Kelvin waves which propagate eastward along the equatorial and coastal wave guides. Near-surface intraseasonal variations are associated with the first baroclinic mode with typical phase speed of 2.91 ± 0.46 m s-1, while the deeper layer intraseasonal variations are associated with the second baroclinic mode with typical phase speed of 1.59 ± 0.18 m s-1. Moreover, the lag correlations between the zonal winds and the observed currents at the ITF straits further demonstrate the source of intraseasonal variations in the ITF.